2017
DOI: 10.15294/jrer.v6i1.16212
|View full text |Cite
|
Sign up to set email alerts
|

Instrumen Penilaian Diri Kompetensi Klinis Mahasiswa Kedokteran

Abstract: AbstrakPenilaian diri dibutuhkan untuk refleksi diri kompetensi klinis bagi mahasiswa sebagai dasar pengembangan diri. Penilaian diri yang selama ini dilakukan belum mampu secara akurat memberikan gambaran kompetensi klinis mahasiswa. Penelitian bertujuan mengembangkan instrumen yang valid, reliabel, dan efektif untuk melakukan penilaian diri kompetensi klinis. Penelitian menggunakan metode campuran dengan rancangan sekuensial eksploratoris. Penelitian dilakukan dalam 4 tahap. Tahap identifikasi dimensi kompet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These results illustrate a possibility of bias in making an assessment using the google form. However, the statement items that refer to this principle tend to be related to the "construction" aspect of the questions in the test (Novitasari et al, 2017). So, indirectly, this principle is also closely related to the teacher's ability to formulate questions.…”
Section: Perceptions Of Teachers Who Use the G-formmentioning
confidence: 99%
“…These results illustrate a possibility of bias in making an assessment using the google form. However, the statement items that refer to this principle tend to be related to the "construction" aspect of the questions in the test (Novitasari et al, 2017). So, indirectly, this principle is also closely related to the teacher's ability to formulate questions.…”
Section: Perceptions Of Teachers Who Use the G-formmentioning
confidence: 99%
“…The Society of Acute Medicine (SAM) guidelines indicated that all medical patients should be assessed within 4 hours of referral (Holland & El-Khaleq, 2018). Novitasari's study stated that referring patients to colleagues who have higher competence indicates of the physicians' understanding of their competence (Novitasari, Ridlo, & Kristina, 2017).…”
Section: Dicussionmentioning
confidence: 99%
“…Students can self-evaluate and assess their strengths and weaknesses for improvement and improvement in further competencies. ( Novitasari , A., et al ., 2017).…”
Section: Figure 2 Presentation Of the Range Of Values 80-99 Of Each S...mentioning
confidence: 99%